Cassava for shrimp feed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
New ways of processing cassava roots are providing a growing international market for the crop as a food for shrimps.]' is proving useful as a shrimp feed because cassava starch s~ranules are elongated and provide agglutinant properties to hold feed...